PREVALENCE OF NON-ALCOHOLIC FATTY LIVER DISEASE, CLINICAL AND LABORATORY MARKERS - Abror Khamrayev; Dilnavoz X. Yuldasheva (Central Asian Journal of Medicine, 2022)
Aim of the research. To determine the clinical and laboratory features of non-alcoholic fatty liver disease at the stage of fatty hepatosis and steatohepatitis. Materials and methods. To solve the set tasks, 98 patients with non-alcoholic fatty liver disease (NAFLD) were examined, including 67 (68.3%) patients at the stage of hepatic steatosis (HS) and 31 (31.6%) patients with steatohepatitis (SH). Of these, 45 (46%) men and 53 (54%) women aged 20 to 75 years (average age 49.2 ± 4.2). Results. With steatohepatitis, higher ALT and AST values are noted than in patients with hepatic steatosis. The article contains clinical features and prognosis in patients with fatty hepatosis and non-alcoholic steatohepatitis (SG). Dyslipidemia (hypertriglyceridemia, decreased HDL, increased LDL) occurs in about 65-85% of patients. The basal insulin level, according to the results of our studies, in persons with NAFLD at the stage of steatosis and steatohepatitis was significantly increased. Conclusion. The risk of developing clinical and laboratory signs of steatosis and steatohepatitis in non-alcoholic fatty liver disease is predicted. Clinical, laboratory signs and basal insulin levels were higher with steatohepatitis than with steatosis.